2017
DOI: 10.1007/s11325-017-1594-2
|View full text |Cite
|
Sign up to set email alerts
|

The utility of home sleep apnea tests in patients with low versus high pre-test probability for moderate to severe OSA

Abstract: HSATs should be reserved for individuals with high pre-test probability for moderate to severe disease as opposed to any individual with suspected OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Demand for at-home sleep testing and HSATs has increased since the coronavirus 2019 (COVID-19) pandemic 14 . However, whether HSATs can replace in-lab PSG remains a topic of controversy owing to concerns about their performance 15 ; in particular, they often do not measure EEG, EOG, or chin EMG, causing difficulty in accurately measuring sleep stages and cortical arousal 16 , 17 . A recent meta-analysis of HSAT accuracy showed that the apnea–hypopnea index (AHI) assessment with HSAT has a significant number of false negatives and false positives, with significant interproduct variability 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Demand for at-home sleep testing and HSATs has increased since the coronavirus 2019 (COVID-19) pandemic 14 . However, whether HSATs can replace in-lab PSG remains a topic of controversy owing to concerns about their performance 15 ; in particular, they often do not measure EEG, EOG, or chin EMG, causing difficulty in accurately measuring sleep stages and cortical arousal 16 , 17 . A recent meta-analysis of HSAT accuracy showed that the apnea–hypopnea index (AHI) assessment with HSAT has a significant number of false negatives and false positives, with significant interproduct variability 18 .…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors contribute to the poor diagnosed prevalence. Portable sleep monitor is a cost-effective alternative to PSG, but it is still more expensive and complicated compared with questionnaire survey, and it may underestimate the severity of OSA and potentially yield false-negative results ( 8 ). Thus, a simple screening tool for moderate-to-severe OSA is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…A review pointed out that HSAT for detecting severe OSA syndrome was AUC 0.80 (95% CI, 0.78 to 0.82) and 0.83 (95% CI, 0.77 to 0.90). [18,19]…”
mentioning
confidence: 99%